Market shares in two-sided media industries - Hans Jarle Kind; Frank Stähler (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper generalizes the frequently used Hotelling model for two-sided markets in order to determine the equilibrium market shares. We show that advertisement levels depend neither on the media price nor on the location of the media firm. An increase in advertising revenues does not change location but only the media price. If the distribution of consumers is asymmetric, market shares will be asymmetric as well, and the media firm with the larger market share charges the higher media price. The larger firm makes a higher profit per reader and in aggregate compared to its smaller rival.
Keywords: D43; 330; Hotelling; general density function; media; location; Medienökonomik; Oligopol; Marktstruktur; Marktanteil; Hotelling Modell; Theorie